Polygamy and sublime passion : sexuality in China on the verge of modernity - McMahon, Keith (University of Hawaiʻi Press, 2010)
For centuries of Chinese history, polygamy and prostitution were closely linked practices that legitimized the 'polygynous male, ' the man with multiple sexual partners. Despite their strict hierarchies, these practices also addressed fundamental antagonisms in sexual relations in serious and constructive ways. Qing fiction abounds in stories of female resistance and superiority. Women - main wives, concubines, and prostitutes - were adept at exerting control and gaining status for themselves, while men indulged in elaborate fantasies about female power. This book introduces a new concept, 'passive polygamy, ' to explain the unusual number of Qing stories in which women take charge of a man's desires, turning him into an instrument of female will.